Calculation of Freezing Heat Load of Catches on Refrigeration Machines of KM. Sumber Natuna in Natuna Waters Province of Kep. Riau - Ade Hermawan; Teguh Binardi; Sony Uji Permana; Istianto Budhi Rahardja (Journal of Applied Sciences and Advanced Technology, 2019)
Refrigeration is the process of absorption of heat from the room with high temperature and transfer the heat to a certain medium. Application of refrigeration is used to maintain the quality of a product, foodstuff, medicine, air conditioning and others. In the world of refrigeration fisheries are used to maintain the quality of the catch so that its economic value and nutritional value is maintained up to the hands of consumers. In general, the main component of refrigeration is divided into five namely compressor, condenser, receiver, expansion valve, evaporator. One of the components that has a role in heat absorption is the evaporator. Evaporator function for evaporation process of refrigeration material. The low-pressure refrigeration vapor is sucked from the evaporator into high-pressure, high-temperature refrigeration vapor. Then through the condenser the steam is condensed (heat exchange) so that the refrigerant vapor becomes high-pressure and normal temperature refrigerant liquids. Heat exchange can be through three ways: by air, water or air + air. After that the liquid refrigerant dropped the pressure on the expansion valve so that the high-pressure refrigerant liquid becomes low. Then on the evaporator component refrigerant material evaporated, in this process the absorption of heat in the product occurs so that the product can be cool temperatures even frozen. The larger the heat is absorbed in the evaporator, then the work on the refrigeration machine is also getting bigger. Based on research in one trip, the heat load at KM. Natuna source reached 147,716.9 kJ / hour. Associated with the fuel consumption of the generator drive motor in a single trip KM. Sumber Natuna reached 2.14 tons.